CHARACTERISTICS OF HEALTHY VASCULAR AGEING (HVA) AND EARLY VASCULAR AGEING (EVA) IN GENERAL POPULATION. EH-UH STUDY (CROATIAN SCIENTIFIC FOUNDATION). (April 2021) - Glavic, Mihaela Marinovic; Blagus, Luka; Bosnjak, Vito; Frkanec, Stjepan; Katic, Luka; Domislovic, Viktor; Matasin, Marija; Kos, Jelena; Vrkic, Tajana Zeljkovic; Pecin, Ivan; Jelakovic, Ana; Premuzic, Vedran; et al.
Abstract : Objective: Arterial stiffness (cfPWV) is acknowledged biomarker of ageing. It was reported that ePWV correlated almost identical with the measured cfPWV and had significant predictive value for cardiovascular (CV) events in hypertensive patients. In a subgroup of population ageing process is faster (EVA), while slower in subjects with HVA). Our aim was to analyze characteristics of EVA and HVA in general Croatian population using ePWV. Design and method: In a stratified random sample of 1087 subjects from the general Croatian adult population which was enrolled in a nationwide survey (EH-UH 1) from 2000–2005 analyses on ePWV were done and subjects were followed-up for 17 years. ePWV was calculated using this formula: ePWV = 9.587–0.402 × age+4.560 × 10-3 × age2–2.621 × 10-5 × age2 × MBP+3.176 × 10-3 × age × MBP-1.832 × 10-2 × MBP. MBP = (DBP)+ 0.4 (SBP - DBP). HVA was defined as the lowest 10% and EVA as the highest 10% of the standardized PWV distribution, adjusted for age quintiles. Subjects with MI, stroke/TIA and DM were excluded. Mortality data were collected from National Public Health Institute records. Results: Subjects with EVA were older with higher systolic/diastolic BP, heart rate and ePWV, more obese, having more frequently dyslipidemia and hypertension, were less educated and less physically active (all p < 0.001). Contrary to women, EVA in men was not associated with age, obesity, level of education and dyslipidemia (p > 0.05). In the whole group, and in both gender, there were no differences between HVA and EVA in income, smoking, alcohol consumption, residency (urban vs.rural; continental vs. Mediterranean) (p > 0.05). More women than men had HVA till the menopause (X2 = 13.867;p = 0.001) but after that we failed to find difference between genders. There were significantly more CV/stroke deaths in EVA vs. HVA in the women (X2 = 8.743; p = 0.003) but not in men. Conclusions: High BP and heart rate, and physical inactivity were found to be associated EVA in both gender. Obesity, older age (menopause), dyslipidemia and lower level of education were characteristics of EVA in women but not in men. EVA in women but not in men was associated with more CV/stroke deaths.